Togo : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1998)
This Selected Issues paper examines civil service employment and reform in Togo. The paper analyzes overall developments in civil service employment and wages. It looks in some detail at employment in the health and education sectors, which together account for almost two-thirds of the civil service, and identifies some of the key problems that also apply to personnel management in other areas. The paper identifies some of the major problems facing civil service management in Togo, and examines the revitalized reform efforts intended to resolve them. Public enterprise reforms in Togo are also examined.